Molecular remodeling of left and right ventricular myocardium in chronic anthracycline cardiotoxicity and post-treatment follow up - Lenčová-Popelová, Olga; Jirkovský, Eduard; Mazurová, Yvona; Lenčo, Juraj; Adamcová, Michaela; Šimůnek, Tomáš; Geršl, Vladimír; Štěrba, Martin (PloS one, 2014)
Chronic anthracycline cardiotoxicity is a serious clinical issue with well characterized functional and histopathological hallmarks. However, molecular determinants of the toxic damage and associated myocardial remodeling remain to be established. Furthermore, details on the different propensity of the left and right ventricle (LV and RV, respectively) to the cardiotoxicity development are unknown. Hence, the aim of the investigation was to study molecular changes associated with remodeling of the LV and RV in chronic anthracycline cardiotoxicity and post-treatment follow up. The cardiotoxicity was induced in rabbits with daunorubicin (3 mg/kg/week for 10 weeks) and animals were sacrificed either at the end of the treatment or after an additional 10 weeks. Daunorubicin induced severe and irreversible cardiotoxicity associated with LV dysfunction and typical morphological alterations, whereas the myocardium of the RV showed only mild changes. Both ventricles also showed different expression of ANP after daunorubicin treatment. Daunorubicin impaired the expression of several sarcomeric proteins in the LV, which was not the case of the RV. In particular, a significant drop was found in titin and thick filament proteins at both mRNA and protein level and this might be connected with persistent LV down-regulation of GATA-4. In addition, the LV was more affected by treatment-induced perturbations in calcium handling proteins. LV cardiomyocytes showed marked up-regulation of desmin after the treatment and vimentin was mainly induced in LV fibroblasts, whereas only weaker changes were observed in the RV. Remodeling of extracellular matrix was almost exclusively found in the LV with particular induction of collagen I and IV. Hence, the present study describes profound molecular remodeling of myocytes, non-myocyte cells and extracellular matrix in response to chronic anthracycline treatment with marked asymmetry between LV and RV.
Keywords: Intermediate Filaments; troponin T; Anthracyclines; Daunorubicin; echokardiografie; Ventricular Remodeling; Transcription Factors; Echocardiography; Blotting, Western; intermediární filamenta; zvířata; Immunohistochemistry; imunohistochemie; daunomycin; antracykliny; Male; králíci; Real-Time Polymerase Chain Reaction; myokard; Troponin T; transkripční faktory; Animals; Myocardium; western blotting; mužské pohlaví; remodelace komor; Rabbits; kvantitativní polymerázová řetězová reakce